2021
DOI: 10.1186/s13075-021-02437-7
|View full text |Cite
|
Sign up to set email alerts
|

Increase of aerobic glycolysis mediated by activated T helper cells drives synovial fibroblasts towards an inflammatory phenotype: new targets for therapy?

Abstract: Background A dysregulated glucose metabolism in synovial fibroblasts (SF) has been associated with their aggressive phenotype in rheumatoid arthritis (RA). Even though T helper (Th) cells are key effector cells in the propagation and exacerbation of synovitis in RA, little is known about their influence on the metabolism of SF. Thus, this study investigates the effect of Th cells on the glucose metabolism and phenotype of SF and how this is influenced by the blockade of cytokines, janus kinases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…Furthermore, we have previously shown that chronic stimulation of SF not only resulted in the development of an "inflammatory memory", but also in that of a "glycolytic memory". On top of an enhanced secretion of IL-6 and MMP3, repeated stimulation of SF with ThCM triggered a significantly increased glycolytic activity as compared to unstimulated, singly stimulated or even restimulated SF [40]. A dysregulated glucose metabolism in SF has been suggested to play a critical role in the pathogenesis of RA [59] and tofacitinib has been shown to suppress the glycolytic activity of RASF [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we have previously shown that chronic stimulation of SF not only resulted in the development of an "inflammatory memory", but also in that of a "glycolytic memory". On top of an enhanced secretion of IL-6 and MMP3, repeated stimulation of SF with ThCM triggered a significantly increased glycolytic activity as compared to unstimulated, singly stimulated or even restimulated SF [40]. A dysregulated glucose metabolism in SF has been suggested to play a critical role in the pathogenesis of RA [59] and tofacitinib has been shown to suppress the glycolytic activity of RASF [37].…”
Section: Discussionmentioning
confidence: 99%
“…An inflammatory microenvironment not only induces a shift in SF phenotype towards inflammation and cartilage and bone destruction, but also leads to the imprinting of this aggressive phenotype, attributed at least in part to epigenetic modifications [20,57]. Remarkably, a pro-inflammatory memory has been described for SF primed by an inflammatory stimulus [58], and chronic stimulation of SF by ThCM triggered a significantly enhanced inflammatory memory response as compared to a single or even a second stimulation [40]. Hence, to be effective, any therapeutic option should be able to suppress the pro-inflammatory memory response of chronically activated SF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, fibroblast metabolic and inflammatory memory seem to be closely associated. While metabolic memory in FLS and retinal pericytes is able to induce a persistent proinflammatory phenotype, activated T cells have been shown to reprogram fibroblast metabolism in inflammatory rheumatoid arthritis [ 90 , 112 ]. The way in which positional memory confers site-specific fibroblast behaviours and links to other environmental adaptations is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Cav-1 causes CAF metabolic reprogramming to aerobic glycolysis, mitochondrial dysfunction and increased autophagy/mitophagy, which propagates to neighbouring CAFs and promotes the anabolic growth of adjacent cancer cells [ 111 ]. Notably, in rheumatoid arthritis, T helper cells have been shown to reprogramme fibroblasts to a glycolytic phenotype [ 112 ], suggesting that fibroblast metabolic reprogramming is a common feature in cancer and inflammatory diseases. Similarly, this phenotype can be further induced and maintained by autocrine TGF-β signalling and is able to spread to adjacent fibroblasts through paracrine signalling [ 111 ].…”
Section: Metabolic Memorymentioning
confidence: 99%